Implementación de políticas públicas del deporte en el Gobierno Autónomo Descentralizado y su influencia en el fomento y desarrollo de política deportivas saludables en los habitantes del cantón Calvas desde enero 2012 a enero del 2013. Lineamientos alternativos - Jumbo Sarango, Jorge Jonathan (2014)
He present study was aimed to investigate the implementation of public policies in the sport decentralized self-government and their influence on the promotion and development of sports policies in healthy inhabitants of the canton Calvas from January 2012 to January 2013. Alternative guidelines. The objectives that guided the research were determined to know the existence of public policies in sport decentralized self-government for promotion and development of sports activities in the healthy population of bald canton. Specific objectives were raised will make a diagnosis in sports management and implementation of public policies by autonomous governments , determine the impacts of short and long term , including development policies and those obtained sporting achievements , and develop a alternative proposal to the municipal administration of sport management . This paper contains a review of the literature that is based on theory and regulations on the responsibilities of decentralized governments in Ecuador , materials and methods is given to know the methods and techniques and procedures used in the process of research results consist charts and graphs and the corresponding analysis of each of them, the discussion proceeds to contrast the theoretical with the empirical and enable the testing of the hypothesis , then the conclusions arising from the fulfillment of the objectives proposed and finally the alternative guidelines in which policies should be implemented in a decentralized government of the Cantòn Calvas on recreational sport arise